Cost‐efficient nonisolated three‐port DC‐DC converter for EV/HEV applications with energy storage. (17th June 2019) - Suresh, Kothandan; Chellammal, Nallaperumal; Bharatiraja, Chokkalingam; Sanjeevikumar, Padmanaban; Blaabjerg, Frede; Nielsen, Jens Bo Holm
Summary: Electric vehicle (EV) systems are the promising future transportation system as they play a key role in reducing the atmospheric carbon emission, and it becomes the focal point of research and development in the current epoch. This paper presents the design and development of three‐port dc‐dc buck‐boost converter (TPB 2 C) applicable for EV. The main feature of the proposed converter is its ability to handle diversified energy sources of different voltage and current characteristics with high output gain. The designed single stage converter with reduced components count can be operated in buck, boost, and buck‐boost mode with partial bidirectional power flow capability. In addition, the TPB 2 C converter could provide buck and boost output simultaneously unlike its counterparts which can output either buck or boost output. In buck mode, the suggested topology charges the battery and thereby eliminates a separate battery management system. Roof top photovoltaic panel and battery are the two input sources for the suggested converter. A small‐signal model of the converter is developed using state‐space approach, and the steady‐state performance of the converter is analyzed comprehensively. The device level simulations carried out in MATLAB‐Simulink and the experimental laboratory prototype model are validated using a dSPACE1104 real‐time digital controller.